PENGARUH MEDIA PUZZLE TERHADAP KEMAMPUAN PENJUMLAHAN KELAS I SDN KEBALEN 02 - Calya Sadira Anjani; Apriyanti Widiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics is frequently regarded as a difficult subject by elementary school pupils, especially when they are asked to grasp the abstract idea of addition. A similar situation was found in grade I D of SDN Kebalen 02, where pupils' addition skills still required strengthening because the teacher had not yet made optimal use of concrete learning media. This study therefore asks whether puzzle media influences the addition ability of grade I pupils at SDN Kebalen 02, with the aim of describing how the use of puzzle media affects their addition ability. A quantitative approach was applied through a pre-experimental one group pretest-posttest design. The sample comprised 33 grade I D pupils selected by purposive sampling. Data were gathered using an addition ability test administered at the pretest and posttest stages. After the Shapiro-Wilk test indicated that the data were not normally distributed, the hypothesis was examined using the Wilcoxon Signed Rank Test at a significance level of 5 percent. The pupils' mean score rose from 83.03 at pretest to 98.79 at posttest following the puzzle-based treatment. The Wilcoxon test produced an Asymp. Sig. (2-tailed) value below 0.001 (less than 0.05), so H0 was rejected and H1 accepted. The findings indicate that puzzle media is effective for improving the addition ability of grade I pupils at SDN Kebalen 02.